Rossiysko-gemanskie raboty v Arktike : 15 let issledovaniy v vysokikh shirotakh (Russian German works in the Arctic: 15 years' research at hight latitudes, in Russian) - Lisitzin, Aleksandr P.; Thiede, Jörn; Kassens, Heidemarie (RAN, 2011)
Fifteen years ago, Russian and German earth scientists began their joint studies of the Laptev, Kara, and Barents seas and the Central Arctic. In the course of these studies, more than 50 marine expeditions and several expeditions to islands and the mainland were accomplished. The organization and results of these studies, as well as the plans for the future, are discussed in the article published below.